Teacher Professional Learning in Religious and Moral Education: Conditions Affecting its Effectiveness at St. Ambrose College of Education in Ghana - Charles Kofi Twene; Konadu Adam; Dorcas Amedorme (Noyam Journals, 2023)
Like specialized teachers in any field of education, teachers of Religious and Moral Education (RME) require exclusive quality skills, expertise and strategies to provide effective delivery of lessons in the field. At St. Ambrose College of Education in the Dormaa East District in the Bono Region of Ghana, Teacher Professional Learning (TPL) is given greater attention. Nonetheless, TPL has been insufficient for improving teaching and learning in RME as expected. The study attempted to investigate the insufficiency of the TPL model for instructional delivery in RME and seeks to offer suitable suggestions and recommendations. Data for the study was collected from the four (4) RME teachers in the college using interviews and the researchers' observations. The results indicated that some conditions in St. Ambrose College of Education are responsible for the insufficient TPL outcomes in RME. These include a lack of innovative teaching approaches exclusive to the field, the college leadership's belief in the use of a confessional approach in teaching RME, the inadequacy of instructional time in the field, and the communication gap between teachers. To address these, it was suggested that enactment strategies used by RME teachers should be content-focused, based on active learning, collaboration, modeling, and coaching by experts. The study adds to the literature on the course structure in the course structure of Ghanaian Educational system.